Revisiting the Aid – Growth Nexus: New Evidence on 56 Least Developed Countries - SUGIYANTO, Eko; DIGDOWISEISO, Kumba (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
Many scholars have observed the aid – growth nexus with no consensus regarding the results. This study tries to investigate the potential non-linearities relationship between aid and growth as well as to explore whether aid is more effective in countries with good policies. In the panel specifications, we use six time periods in 56 Least Developed countries, namely: 1985-1989; 1990-1994; 1995-1999; 2000-2004; 2005-2009; 2010-2014. By using the panel Generalized Method of Moments (GMM) estimation, we find that a more positive impact of aid on growth in good policy environments is not a robust result in all models. However, our study confirms a non-linear relationship between aid and growth .